Understanding Tri Pantangan and Organizational Culture on Accounting Fraud - Wardani, Dewi Kusuma; Yiping, Yiping (Journal of Economic, Management, Accounting and Technology (JEMATech), 2025)
Accounting fraud is a serious problem that can harm a company financially, and can even damage the reputation and credibility of an organization. In this context, understanding the tri pantangan is expected to strengthen integrity and prevent behavior that can end in accounting fraud. In addition, an organizational culture that supports transparency, accountability, and good business ethics is also believed to minimize the potential for fraud. To find out how much influence knowledge of the Three Taboos and corporate culture has on accounting fraud is the main objective of this study. Using primary data collected from a survey sent using Google Forms, this study uses a quantitative approach. We received 111 responses in total. Big Data analysis using SPSS 26 was used to process the data. This study found that accounting fraud was negatively affected by an understanding of the Tri Pantangan, while accounting fraud was not affected by organizational culture.